Multi-modal analysis of barely visible impact damage in carbon fibre composites through the fusion of pulsed thermography and phased array ultrasonic testing - Torbali, Muhammet E.; Zolotas, Argyrios; Avdelidis, Nicolas P.; Ibarra-Castanedo, Clemente; Maldague, Xavier P. (Taylor & Francis, 2026)
The increasing use of composite materials in modern aircraft structures has necessitated more efficient and reliable inspection techniques to ensure structural integrity and operational safety. Barely visible impact damage (BVID) poses a significant challenge in composite maintenance due to its subtle nature, requiring advanced non-destructive testing and evaluation (NDT&E) methods for accurate detection and characterisation. This study explores a multi-modal inspection approach that integrates phased array ultrasonic testing (PAUT) and pulsed thermography (PT) to enhance BVID detection in carbon fibre-reinforced polymer (CFRP) composites. By leveraging complementary fusion strategies, the proposed framework improves defect localisation beyond the limitations of individual techniques. The results demonstrate that fusion increased PAUT-detected sizes by up to 7% for thin specimens and 8% for thick ones, while PT-detected sizes improved by as much as 71% and 53%, respectively. These findings highlight the synergistic advantages of multi-modal NDT&E, showcasing its potential to provide complementary defect assessment and reduce uncertainty in damage evaluation. The results of this study contribute to the development of more sophisticated inspection methodologies, which ultimately support more efficient and reliable maintenance strategies in aviation.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 46 Information and Computing Sciences; 4605 Data Management and Data Science; 4016 Materials Engineering; NDT fusion; barely visible impact damage (BVID); Phased Array Ultrasonic Testing (PAUT); Pulsed Thermography (PT); multi-modal defect detection; combination of NDT techniques